Dependence of acoustic anomalies on chemical composition in strontium barium niobate crystals (from conventional ferroelectric to relaxor) probed by Brillouin light scattering. (4th April 2019) - Pugachev, A. M.; Zaytseva, I. V.; Malinovsky, V. K.; Surovtsev, N. V.; Ivleva, L. I.; Lykov, P. A.
Abstract: Brillouin spectra in a series of strontium barium niobate crystals Sr x Ba1 -x Nb2 O6 of different chemical composition ( x = 0.3, 0.5, 0.6, 0.75) are investigated in various spectral geometries and in a wide temperature ranges including ferroelectric and paraelectric phases. It is shown that for all crystals studied, a pronounced temperature dependences of position and width of the Brillouin lines are clearly manifested only when the acoustic wave vector is parallel to the polar axis Z. Exponential temperature dependence of anomalies of elastic modules was obtained. The exponent rate decreases with increasing of disordering in crystals under study.